Ethical reflections on environmental crisis: Insights from 'the world without us’ - Husein, Sabarina; Widayanti, Sri (Life and Death: Journal of Eschatology, 2024)
Background: This research delves into the book "The World Without Us" by Alan Weisman, exploring the intersection of environmental ethics and the environmental crises arising from human exploitation of nature. Method: The study employs a qualitative literature review methodology, drawing insights from primary and secondary sources to shed light on the ethical dimensions of environmental degradation. Findings: The findings underscore the critical role of environmental ethics in guiding sustainable development practices, emphasizing the need for responsible stewardship of natural resources and the preservation of biodiversity. Conclusion: The article advocates for an ethical framework that integrates environmental considerations into decision-making processes, fostering a sense of responsibility and promoting sustainable development practices that prioritize environmental health, social equity, and long-term well-being. Novelty/Originality in this Study:  By imagining a world without human presence, this study not only explores the impact of human exploitation of nature but also formulates an innovative, ethical framework for sustainable development, challenging how we view human-nature relationships.